2018
DOI: 10.1208/s12249-018-1058-4
|View full text |Cite
|
Sign up to set email alerts
|

Spray-Dried Proliposome Microparticles for High-Performance Aerosol Delivery Using a Monodose Powder Inhaler

Abstract: Proliposome formulations containing salbutamol sulphate (SS) were developed using spray drying, and the effects of carrier type (lactose monohydrate (LMH) or mannitol) and lipid to carrier ratio were evaluated. The lipid phase comprised soy phosphatidylcholine (SPC) and cholesterol (1:1), and the ratios of lipid to carrier were 1:2, 1:4, 1:6, 1:8 or 1:10 w/w. X-ray powder diffraction (XRPD) revealed an interaction between the components of the proliposome particles, and scanning electron microscopy (SEM) showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 80 publications
0
8
0
2
Order By: Relevance
“…Liposomes clearly showed better results than proliposomes. Future studies have to be performed to correct the osmotic effect of mannitol in the proliposome, to substitute the amount of the carrier in the formulation or to replace mannitol by another transporter (e.g., sorbitol, lactose monohydrate, or other lipids in the formulation) [52,53].…”
Section: Resultsmentioning
confidence: 99%
“…Liposomes clearly showed better results than proliposomes. Future studies have to be performed to correct the osmotic effect of mannitol in the proliposome, to substitute the amount of the carrier in the formulation or to replace mannitol by another transporter (e.g., sorbitol, lactose monohydrate, or other lipids in the formulation) [52,53].…”
Section: Resultsmentioning
confidence: 99%
“…Proliposomes are stable formulations that can generate liposomes upon hydration with aqueous phase. Proliposomes are stable powders of carbohydrate coated or mixed with phospholipid, cholesterol and drug using small scale production techniques such as modified rotary evaporators (Payne et al 1986) or large scale methods such as fluid-bed coating (Gala et al 2015) or spray-drying (Omer et al 2018). Alternatively, and as an interest of the present research investigation, the slurry-based method can be used on small or large scales as shown by our research group (Khan et al 2015).…”
Section: Introductionmentioning
confidence: 94%
“…Do tồn tại ở trạng thái rắn nên hầu hết các vấn đề về độ ổn định của liposome được giải quyết và dễ dàng ứng dụng được vào các dạng thuốc rắn. Proliposome có thể được bào chế bằng các phương pháp khác nhau như hydrat hóa màng film, phun sấy, phương pháp đối kháng dung môi siêu tới hạn, phương pháp bao hạt,… [4,5]. Trong nghiên cứu trước, nhóm tác giả đã nghiên cứu bào chế liposome BBR sử dụng các thành phần phosphatidyl choline đậu nành hydrogen hóa (HSPC), natri deoxycholat (NaDC) và vitamin E bằng phương pháp tiêm ethanol [6].…”
Section: Mở đầU *unclassified